Optical to terahertz engineering - Saha, Arijit; Biswas, Arindam 1984-; Ghosh, Kankat; Mukhopadhyay, Nilanjan (Progress in optical science and photonics, 2023)
This book highlights advances in the field of THz engineering along with limitations of radio frequency (RF) technology. All engineering applications have been designed to operate over a specific frequency or wavelength range in electromagnetic spectrum. In recent years, the unexplored domain of THz range of electromagnetic spectrum has paved the way for terahertz technology due to its nonionizing nature and sensitivity to water content. A wide range of applications with THz techniques such as terahertz time-domain spectroscopy (THz-TDS), biological, medical and pharmaceutical sciences, explosives inspection, information and communication technology (ICT) sector and many more, have potential to be the technology of future. Different designing aspects and evolving application areas are addressed to enrich the technical knowledge of readers. This book provides an overview of state of the art in terms of research and industrial progress in THz spectrum